Online final year project website for FKE UiTM students / Farah Hayati Che Lah - Che Lah, Farah Hayati (2015)
E - Learning carries many benefits over traditional classroom - based instruction. But the decision to adopt e - Learning will depend on the needs and capacities of each person. Because of that, Online Final Year Project Management System is created especially for Electrical Engineering Faculty (FKE), UiTM Shah Alam to overcome the constraint between students and supervisors. Traditionally, students will update their final year project progress to their supervisors by weekly. All of the progress will be reported in the log book of each student and endorsed by their supervisor respectively. Due to this situation, students find it difficult to allocate some time to meet with their supervisors, as long as supervisor needs to spend some certain period to discuss with their students. The methodology is used in this paper were to implemented a common website in organizing final year project management system which operated using Joomla!®3.4. In conclusion, the goal of this paper is to ease the final year project management through online website.